Occupational exposure to ultrafine particles and lung cancer in a population exposed to asbestos - Carine Rostello; Céline Gramond; Sabyne Audignon; Isabelle Thaon; Patrick Brochard; Julia Benoist; Antoine Gislard; François Laurent; Christophe Paris; Pascal Andujar; Bénédicte Clin; Jean-Claude Pairon; et al. (BMC Public Health)
Abstract Background Ultrafine particles are present in ever greater quantities in the workplace and only one epidemiological study to date has found an association with the occurrence of lung cancer. Objective To investigate the effect of occupational exposure to ultrafine particles on the risk of lung cancer. Methods The ARDCO is a surveillance program involving retiree workers who had been exposed to asbestos during their working life. Exposure to ultrafine particles over the complete lifetime occupational history was assessed using the French job exposure matrix MATPUF. Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CI). Results There was no association between exposure to ultrafine particles and lung cancer after adjustment for smoking and exposure to asbestos and crystalline silica. Conclusion The findings do not indicate increased risks of lung cancer for UFP after adjustment for level of exposure to asbestos, crystalline silica, and smoking status. Clinical trial number Not applicable.